A retrospective multicentre study on dalbavancin effectiveness and cost-evaluation in sternotomic wound infection treatment: DALBA SWIT Study. (September 2022) - Pascale, Renato; Maccaro, Angelo; Mikus, Elisa; Baldassarre, Maurizio; Tazza, Beatrice; Esposito, Fabio; Rinaldi, Matteo; Tenti, Elena; Ambretti, Simone; Albertini, Alberto; Viale, Pierluigi; Giannella, Maddalena; et al.
ABSTRACT: Objective: To evaluate the cost-effectiveness of dalbavancin compared with standard of care (SoC) treatment as daptomycin or teicoplanin in patients with sternal wound infections (SWI). Methods: Multicentre retrospective study of patients diagnosed with SWI from January 2016 to December 2019 at two cardiac surgery facilities treated with dalbavancin, teicoplanin or daptomycin. Patients with SWI treated with dalbavancin were compared with SoC to evaluate resolution of infection at 90 and 180 days from infection diagnosis, length of stay (LoS) and management costs. Results: 48 patients with SWI were enrolled, 25 (50%) male, median age 67 (60–73) years, Charlson index score 5 (4–7). Fifteen patients were treated with dalbavancin (31%) and 33 with SoC (69%): teicoplanin in 21 (63%), and daptomycin in 12 (37%). Staphylococcus species were the most frequent isolates (44, 92%), mostly (84%) resistant to methicillin. All patients were treated with surgical debridement followed by negative pressure wound therapy. Wound healing at day 90 and 180 was achieved in 46 (95.8%) and 34 (82.9%) of patients, respectively. A shorter length of hospitalization in patients treated with dalbavancin compared with SoC [12 (7–18) days vs 22 (12–36) days, p:0.009] was found. Treatment with dalbavancin resulted in total cost savings of €16 026 (95% CI 5976–26 076, P < 0.001). Savings were mainly related to the LoS that was significantly shorter in the dalbavancin group, generating significantly lower cost compared to SoC group. Conclusion: Dalbavancin treatment of sternal wound infections is effective and seems to reduce hospitalization length, leading to significantly lower costs.